Transformational Learning in First-Year Australian Preservice Primary Teacher. (October 2019) - Lummis, Geoffrey; Lock, Graeme; Freeman, Clare; Ferguson, Catherine Anne
The early experience of commencing university students is an important precursor for retention and student success and involves a transformation in learning. This article reports the experiences of commencing students in an Australian Education (Primary) degree. Data were collected using a mixed methods approach, consisting of an online survey, and semistructured interviews. The data revealed that respondents experienced some phases of Mezirow's transformational learning theory. Interviewees were enthusiastic about their future career with high scores in the online instrument for academic orientation and student identity, which indicated that they were experiencing the building of confidence and competence in new roles (Phase 7) and provisionally trying out new roles (Phase 8). Nevertheless, all respondents indicated being overwhelmed by the unexpectedly high academic study load, indicating a disorientating dilemma (Phase 1). These results are placed in the context of student retention and degree completion.